Innovative Wound Management Approaches in Circumcision for Improved Recovery Outcomes - Suhaymi, Ery (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study evaluates the effectiveness of an innovative wound management approach compared to conventional treatment in improving post-circumcision recovery outcomes. Using a randomized controlled trial with 60 children aged 6–12, participants were assigned to an intervention group receiving a hydrogel-based antibacterial dressing with a standardized analgesic protocol, and a control group receiving traditional gauze with standard care. Data were collected through clinical observations, validated pain scales, and structured follow-ups over 14 days, with analyses conducted using independent t-tests and chi-square tests. Results show that the intervention group experienced faster epithelialization, lower postoperative pain, and fewer mild infections than the control group. The study concludes that innovative wound dressing technologies, combined with optimized postoperative care protocols, enhance healing efficiency, patient comfort, and postoperative safety, contributing to evidence-based surgical nursing practice and improved healthcare quality.